Enterovirus 71 outbreak, Brunei - AbuBakar, Sazaly; Sam, I-Ching; Yusof, Jaliha; Lim, Meng Keang; Misbah, Suzana; Mat Rahim, Nor Aziyah; Hooi, Poh-Sim (Centers for Disease Control and Prevention, 2009)
Enterovirus 71 (EV71) outbreaks occur periodically in the Asia-Pacific region. In 2006, Brunei reported its first major outbreak of EV71 infections, associated with fatalities from neurologic complications. Isolated EV71 strains formed a distinct lineage with low diversity within subgeno-group B5, suggesting recent introduction and rapid spread within Brunei.